Due diligence obligations in international law / Alice Ollino. - Ollino, Alice (Cambridge University Press, 2022)
Due diligence obligations are typically described by scholars and practitioners as 'elusive', 'weak', and difficult to pin down in the abstract. Challenging these assumptions, this book offers a systematic reconstruction of the foundations of due diligence obligations of states and explores their nature, rationale, content and scope of operation in international law. Tackling due diligence from a general perspective, this book seeks to complement scholarly studies on public international law obligations and their theory. This book will be relevant for academics, practitioners, graduate students across international law and anyone seeking to better conceptualise due diligence under international law and understand how due diligence obligations are operationalised in practice.